Re‐investigation of lead(II) formate. (4th January 2013) - Lanza, Arianna; Gambirasi, Arianna; Favaro, Monica; Peruzzo, Luca; Chiurato, Matteo; Nestola, Fabrizio
<x xml:space="preserve">Abstract</x> The crystal structure of the title compound, poly[di‐μ4‐formato‐lead(II)], [Pb(HCOO)2]n, has been re‐investigated. It consists of a three‐dimensional polymeric network of Pb2+ nodes connected by bridging formate anions. Despite having been described previously, the structural information available so far [Harrison & Steel (1982). J. Organomet. Chem.239, 105–113] is incomplete and the reported Pnma space group is incorrect. In this work, the space‐group assignment to P212121 is discussed and a complete description of the structural features of lead(II) formate is provided.